Cystathionine β-synthase deficiency in the E-HOD registry - part II: dietary and pharmacological treatment - Morris, Andrew A. M.; Sokolová, Jitka; Pavlíková, Markéta; Gleich, Florian; Kölker, Stefan; Dionisi-Vici, Carlo; Baumgartner, Matthias R.; Hannibal, Luciana; Blom, Henk J.; Huemer, Martina; Kožich, Viktor (Journal of inherited metabolic disease, 2025)
Cystathionine β-synthase (CBS) deficiency (classical homocystinuria) has a wide range of severity. Mildly affected patients typically present as adults with thromboembolism and respond to treatment with pyridoxine. Severely affected patients usually present during childhood with learning difficulties, ectopia lentis and skeletal abnormalities; they are pyridoxine non-responders (NR) or partial responders (PR) and require treatment with a low-methionine diet and/or betaine. The European network and registry for Homocystinurias and methylation Defects (E-HOD) has published management guidelines for CBS deficiency and recommended keeping plasma total homocysteine (tHcy) concentrations below 100 μmol/L. We have now analysed data from 311 patients in the registry to see how closely treatment follows the guidelines. Pyridoxine-responsive patients generally achieved tHcy concentrations below 50 μmol/L, but many NRs and PRs had a mean tHcy considerably above 100 μmol/L. Most NRs were managed with betaine and a special diet. This usually involved severe protein restriction and a methionine-free amino acid mixture, but some patients had a natural protein intake substantially above the WHO safe minimum. Work is needed on the methionine content of dietary protein as estimates vary widely. Contrary to the guidelines, most NRs were on pyridoxine, sometimes at dangerously high doses. tHcy concentrations were similar in groups prescribed high or low betaine doses and natural protein intakes. High tHcy levels were probably often due to poor compliance. Comparing time-to-event graphs for NR patients detected by newborn screening and those ascertained clinically showed that treatment could prevent thromboembolism (risk ratio 0.073) and lens dislocation (risk ratio 0.069).
Gesehen am 26.11.2025